Students' preferences for strategies to facilitate self-directed learning in distance education in Taiwan - Tsay, Mei-Huei, author; Morgan, George A., advisor; Barber, Clifton, E., committee member; Jansen, Duane G., committee member; Griego, O. M., committee member (Colorado State University. Libraries, 1999)
The purpose of this study is to determine perceptions of the National Open University [NOU, Taiwan, Republic of China] students' preferences for strategies to facilitate self-directed learning and to see if there are relationships to their background characteristics. An instrument was developed from current literature to quantify background characteristic variables and facilitating strategy preferences. The 1500 potential subjects, both current and inactive students, were obtained from through a random sampling procedure. A 42 percent return rate was obtained. Results for the study showed that there were significant differences between current and inactive NOU students' characteristics on age, duration of studying at NOU, declaration of a major, duration of full-time work experience, internal motivation, insight about self, self-directed learning readiness. Although current and inactive students did not differ on any of the five self-directed learning facilitating preference scales, they did differ on five items; i.e., instructors' attitudes about the goal of education, assignment marking style, student's self-directed learning potential, learning-contract based evaluation criteria, and personal-responsibility focused evaluation asset. The study also found students with higher internal motivation, external-payoff motivation, insight about self, and self-directed learning readiness scores tended to prefer more assistance/styles from the five students' self-directed learning preference scales, except no relationship was founded between students' insight about self and institution provided orientation programs. Female students preferred more services/styles listed within the five students' self-directed learning preference scales except no difference was found for course design adaptations. Furthermore, students who had been studying at NOU longer required less assistance from the institution. In predicting students' preferences for institution support services, duration of studying and full-time work experiences, internal and external-payoff motivations, and self-directed learning readiness, combined to be predictors. of these predictors, students' who had been studying at NOU longer and who had more full-time work experiences required less assistance from NOU. Students' preferences for institution-provided orientation programs was predicted by the combination of female gender, and internal and external-payoff motivations while the preferences for instructional styles were predicted by the combination of female gender, and internal and external-payoff motivations, and self-directed learning readiness. The combination of shorter period for studying at NOU and internal and external-payoff motivations predict students' preferences for interpersonal interactions. And finally, students' preferences for course design adaptation was predicted by internal and external-payoff motivations and students' self-directed learning readiness. The study provides a framework, which can be used as a diagnostic and facilitating tool for distance adult learning organizations and professionals to enhance the effectiveness of self-directed learning facilitation and reduce the dropout/stopout rate.
Keywords: adult education; continuing education; educational technology